I do not care if we go down in history as barbarians [videorecording (DVD)] - Jude, Radu, 1977-; Jude, Radu, 1977-; Iacob, Ioana, 1980-; Bogdan, Alex, 1986-; Dabija, Alexandru, 1955- (Big World Pictures, 2020)
City officials and others feel threatened when a young theater director tries to stage an accurate re-enactment of the 1941 Odessa massacre, in which Romanian soldiers slaughtered thousands of Ukrainian Jews.